Potensi Manfaat Sertifikasi Halal Terhadap Produk UMKM - Mush'ab, Muhammad (Kasaba, 2021)
As a Muslim, he is not allowed to consume and produce freely without any restrictions, so Islam regulates that, that is, a product must be halal and thayyib. then the halal certificate becomes clear evidence of these two things. There are so many benefits if a product has a halal certificate, a sense of security and comfort felt by consumers as product connoisseurs, when consumers are comfortable, the selling power of the product will increase. Therefore, the government makes regulations related to the halal guarantee of a product by issuing a law on halal guarantee, so the government as the regulator guarantees the halalness of a product. then a micro, small and medium-sized enterprise which is the biggest economic driver of Indonesia can improve the quality of its business by obtaining the halal certificate. the benefits obtained are not only at the national level but also at the global level Many countries in the world are looking at the potential of the halal industry, therefore many of them have made a vision in the following years to be able to dominate the global halal market. the participation of micro-entrepreneurs who already have this certificate is only 20% of the total, so more awareness is needed for these business actors because the benefits obtained are very large, there are real examples related to the benefits of this certification, one of which is an increase in business turnover that occurs significant when the business does not have a halal certificate, even more so if it is supported by other factors, namely the large number of Muslims in Indonesia.